Comparative Evaluation of Aqua Regia and Tri-Acid Digestion Methods for the Determination of As, Cu, and Pb in an Ore-Grade Certified Reference Material by Flame Atomic Absorption Spectrometry - Angga Pratama; Selfina Gala (Candela Edutech Indonesia, 2026)
Trace element analysis in ore grade samples is critical for mineral exploration and resource evaluation. The choice of digestion method greatly influences the accuracy of results, which form the basis for mining investment decisions. This study compares the performance of aqua regia (partial digestion) and tri-acid digestion (near-total digestion) methods for determining Arsenic (As), Copper (Cu), and Lead (Pb) concentrations. Measurements were conducted using Flame Atomic Absorption Spectrometry (AAS) with Certified Reference Material (CRM) as a validation standard, while statistical analysis was performed using the Wilcoxon Signed-Rank Test. Results show complementary performance between the two methods. Aqua regia provided the best accuracy for As (recovery 100.19%, bias 0.19%), but systematically overestimated Cu (bias 14.19%) and Pb (bias 14.14%). In contrast, tri-acid digestion delivered superior accuracy for Pb (recovery 101.27%, bias 1.27%) and better results for Cu (bias 4.83%), yet overestimated As (bias 12.25%). Statistical tests confirmed that only Pb by tri-acid (p = 0.7213) and As by aqua regia (p = 0.8785) showed no significant difference from CRM values. Operationally, aqua regia is more advantageous due to shorter digestion time (2 hours), lower cost, and better safety. Tri-acid digestion requires a longer time, higher cost, and strict safety protocols due to HF usage. This study concludes that digestion method selection should follow the fit-for-purpose principle based on target elements, sample matrix, and laboratory capabilities.